Germination and interspecific grafting of passion fruit - Silva, Roseano Medeiros da; Aguiar, Ana Verônica Menezes de; Garcia, Kaio Gráculo Vieira; Faleiro, Fábio Gelape; Mendonça, Vander; Cardoso, Eudes de Almeida (Comunicata Scientiae, 2018)
The objective of this study is to evaluate the seed germination and efficiency of grafting yellow passion fruit on six Passifloraceae species. The species used as rootstocks were Passiflora foetida L., P. cincinnata Mast., P. ligularis Juss., P. caerulea L., P. gibertii N. E. Brown, and P. edulis Sims. The study involved six treatments with four replicates of eight plants per plot and was arranged in a completely randomized block design. The seedlings were produced on a non-sterile substrate composed of a mixture of soil and bovine manure at the ratio of 3:1. The percentage of germination was high for all studied species, and the rate of graft development and survival was higher than 70 and 85.71%, respectively, within 60 days after grafting.